ARCHIPELAGIC CALENDAR IN THE JAVANESE AND BUGIS MANUSCRIPTS - Hikmatul Adhiyah Syam (Fakultas Syari'ah dan Hukum UIN Walisongo, 2022)
Manuscripts of the Javanese and Bugis calendars are products of the archipelago's culture. It is a fundamental issue with respect to astronomy as a science. This study analyzes the Bugis and Javanese calendars indicated in the manuscripts. Comparative descriptive analysis and literature research methods are both used in this study. According to the article, the Javanese and Bugis have manuscripts relating to the calendar as a way of life-based on natural phenomena. The Lontara Bilang and Lontara Kutika Ugi Sakke Rupa scripts belong to the Bugis people, whereas the Serat Mustaka Rancang and Serat Widya Pradhana manuscripts belong to the Javanese.